The Effect of Litigation Risk on Accounting Conservatism, Leverage & Managerial Ownership as Moderation - Yulita Mustikasari; Anita Wijayanti; Kartika Hendra Titisari (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2020)
Pressures in the competitive business world, directly or indirectly result in companies doing earnings management, conflicts of interest that result in accounting conservatism menyaebabkan tendency economically shareholdersto file a lawsuit (litigation). This study was conducted to examine the effect of the litigation risk accounting conservatism with leverage and managerial ownership as a moderating variable. The population in this study is the retail trading company listed on the Indonesia Stock Exchange from 2013 to 2017. Sampling was purposive sampling method to obtain 21 companies for 5 years. In this study, the type of data is quantitative data, to test the three hypotheses using path analysis with WarpPLS. Based on the results of the analysis indicate that the litigation risk variables affect the accounting conservatism, moderate leverage variable risk of litigation against accounting conservatism, while managerial ownership variable is not moderating variable between the risk of litigation againts accounting conservatism.